ADVERSITY QUOTIENT DAN PENALARAN KREATIF MATEMATIS SISWA SMA DALAM PEMBELAJARAN ARGUMENT DRIVEN INQUIRY PADA MATERI TURUNAN FUNGSI - Wahyu Hidayat (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
This study is designed in the form of experiment with the design of control group and posttest only aimed at investigating the role of learning that Argument Driven Inquiry (ADI) in improving senior high school students’ creative mathematical reasoning ability. The population of this study was senior high school students’ in Cimahi City and the samples were 69 senior high school students’ set purposively and randomly to be included into the experimental class and control class. Based on the results and discussion, it is concluded that: (1) creative mathematical reasoning ability of the students who received Argument Driven Inquiry (ADI) instruction is better than those who received direct instruction is reviewed based on the whole and the type of Adversity Quotient (Quitter / AQ Low, Champer / AQ Medium, and the Climber / AQ High); Learning factors and type of Adversity Quotient (AQ) affect the achievement of creative mathematical reasoning skills students. In addition, there is no interaction effect between learning and AQ together in developing the creative mathematical reasoning ability of students'; (3) creative mathematical reasoning ability of students’ has not been achieved optimally on the indicators novelty.